Analisis Kerentanan terhadap Risiko Krisis Iklim pada Tiga Komunitas: Peternak Sapi, Petani Tadah Hujan, dan Nelayan di Pulau Lombok (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The climate crisis caused by human activity is increasing the frequency and intensity of extreme events such as droughts, floods, and storms, including on Lombok Island, which is heavily dependent on natural resources. This study analyzes the vulnerability levels of three main communities in Lombok: cattle ranchers (East Lombok), rain-fed farmers (Central Lombok), and fishermen (West Lombok). The approach used is the Livelihood Vulnerability Index (LVI), integrated with the Intergovernmental Panel on Climate Change (IPCC) framework, encompassing three main dimensions: exposure, sensitivity, and adaptive capacity. Data were obtained through a survey of 90 respondents selected using stratified random sampling, as well as secondary data from relevant agencies. This method was chosen based on its ability to comprehensively measure vulnerability and compare three distinct livelihood-based communities, which cannot be achieved through other methods such as the CVI or SoVI. The results show that rain-fed farmers have the highest vulnerability with an LVI-IPCC score of 0.03 due to their high exposure to rainfall variability. Cattle farmers have a moderate level of vulnerability with an LVI-IPCC score of -0.0006 due to their high sensitivity to feed and water availability. Fishermen have the lowest vulnerability with an LVI-IPCC score of -0.0017 due to their greater adaptive capacity, including livelihood diversification and social support. These findings indicate that vulnerability levels are strongly influenced by adaptive capacity and dependence on natural resources. Therefore, community-based adaptation strategies need to be developed to strengthen resilience to the climate crisis.